A cross sectional study on determinants of quality of life in ALS. Issue 11 (15th October 2004) - Chiò, A; Gauthier, A; Montuschi, A; Calvo, A; Di Vito, N; Ghiglione, P; Mutani, R
Abstract : Background: Understanding the determinants of quality of life (QoL) in amyotrophic lateral sclerosis (ALS) has become increasingly important with the recent emphasis on the comprehensive management of patients. Objective: To evaluate the determinants of QoL in ALS using two scales with different theoretical constructs: the Schedule for the Evaluation of QoL-Direct Weighting (SEIQoL-DW), which evaluates subjective aspects of QoL, and the McGill QoL Questionnaire (MQOL), which evaluates both health related and non-health related factors of QoL. Methods: Eighty consecutive patients with ALS underwent a battery of tests evaluating QoL and a series of physical, emotional, psychological, and socioeconomic predictor variables. A stepwise linear regression model was used to compare QoL scores and explicatory variables. Results: SEIQoL-DW score was related to social support, depression, religiosity, and socioeconomic status. Total MQOL score was related to social support, socioeconomic status, and clinical status. MQOL single item score (MQOL-SIS) was related to social support, depression, social withdrawal, and socioeconomic status. SEIQoL-DW score was not related to total MQOL score. Conversely, a significant correlation was found between SEIQoL-DW and MQOL-SIS. Conclusions: With both QoL scales, the most important explicatory variable of QoL was the self perceived quality of social support. Physical status was not relevant in determining QoL. This study indicates that health related QoL measures are not adequate to assess QoL in patients with ALS, because their appreciation of QoL mainly relies on psychological, supportive, and spiritual factors. Therapeutic interventions should consider the psychological needs of patients and pay greater attention to caregivers' issues.